STRATEGI KEPEMIMPINAN DALAM MANAJEMEN PENDIDIKAN DI ERA DIGITAL: MEMAHAMI MANUSIA DAN TEKNOLOGI - Indriana Fitriah, Nur; Adriana; Diyah Ayu Kristianti; Azainil; Laili Komariyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The role of digital media is very important because of the development of technology, leaders are required to understand and be sensitive to the use of media in the digital era and implement communication in the organization. Good leadership communication will ensure that each member of the organization can do their job well. Without good and correct communication, it is likely that all processes in the organization cannot run optimally. Becoming a good leader in the current and future millennial generation is a critical challenge. Leadership is the process of influencing and providing direction to an individual or group to be able to achieve the desired goals. Leaders generally have the ability to motivate an individual or group to work with a happy heart so that the vision and mission that have been made can be achieved. With the development of the times, many leaders have emerged due to the demands and environmental conditions that must understand technology. Social media itselfrefers to internet-based applications, including social networks, wikis, blogs, and so on, which are likely to create and share content created by the user.